Mathematical Approaches to Modeling, Optimally Designing, and Controlling Electric Machine - Prakht, Vladimir; Ibrahim, Mohamed N.; Anuchin, Aleksey S. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Optimal performance of the electric machine/drive system is mandatory to improve the energy consumption and reliability. To achieve this goal, mathematical models of the electric machine/drive system are necessary. Hence, this motivated the editors to instigate the Special Issue "Mathematical Approaches to Modeling, Optimally Designing, and Controlling Electric Machine", aiming to collect novel publications that push the state-of-the art towards optimal performance for the electric machine/drive system. Seventeen papers have been published in this Special Issue. The published papers focus on several aspects of the electric machine/drive system with respect to the mathematical modelling. Novel optimization methods, control approaches, and comparative analysis for electric drive system based on various electric machines were discussed in the published papers.